Nonlinear Volterra difference equations in space lp - Michael I. Gil'; Rigoberto Medina (Discrete Dynamics in Nature and Society)
We consider a class of vector nonlinear discrete-time Volterra equations in space lp and derive estimates for the norms of solutions. These estimates give us explicit stability conditions, which allow us to avoid finding Lyapunov functionals.